Non-Uniform Corrosion Monitoring of Steel Pipes Using Distributed Optical Fiber Sensors in the Fluctuation Zone of a Coastal Wharf - Jiguo Chen; Ruiqi Zhang; Qianwu Li; Hongke Wang; Qiangqiang Ma; Qi Fan; Liang Fan; Zequan Lin (Sensors)
Steel pipes, while essential for modern infrastructure due to their high strength and load-bearing capacity, are prone to corrosion in the marine environment, leading to material degradation, compromised structural integrity, and elevated safety risks and economic losses. In this study, distributed fiber-optic sensors were deployed on steel pipe surfaces to monitor corrosion in the splash zone (a region particularly vulnerable to cyclic wet–dry conditions). The sensors were engineered to withstand aggressive marine exposure. Strain variations induced by expansive corrosion products were detected via the fiber-optic array and used to calculate localized mass loss. Color-coded corrosion severity maps were generated to visualize the non-uniform corrosion distribution. Experimental results demonstrate that sensor-derived mass loss values align with 3D laser scanning measurements, validating the operational efficacy of distributed fiber-optic sensing for marine corrosion monitoring. This approach provides quantitative insights into the field applicability of optical sensing in structural health monitoring.